Unraveling the phylogenetic relationships of Nectouxia (Solanaceae): its position relative to Salpichroa - Carrizo García C. (2018)
We are indebted to G. Salazar Chávez (Instituto de Biología, UNAM, Mexico) and F. Chiarini (IMBIV, Argentina) for providing photographs of Nectouxia formosa. We thank the governments of Argentina, Bolivia, Ecuador, and Peru for the permits to do field trips and plant collections. This research was financially supported by grants awarded to G. Barboza and S. Leiva González by Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET, Argentina), Ministerio de Ciencia, Tecnología e Innovación Productiva (MINCYT, Argentina), Agencia Nacional de Promoción Científica y Tecnológica (ANPCyT, Argentina), Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC, Peru), and Secretaria de Ciencia y Tecnología (SECyT-UNC, Argentina).